1990
DOI: 10.1111/j.1945-5100.1990.tb00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Tektite research 1936–1990*

Abstract: — Fifty‐odd years of tektite research are reviewed, proceeding from the discovery of the first North American tektites in 1936. This included the early recognition that tektites were terrestrial objects rather than meteorites and that the glassy particles in tektites were fused quartz (lechatelierite). Later, during National Science Foundation‐supported research, it was found that some tektites appeared to have formed as puddles of melt, that the content and character of bubbles in lechatelierite can be used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Barnes (e.g., Barnes and Pitakpaivan, 1962;Barnes, 1989Barnes, , 1990, mainly from studying Muong Nong-type tektites, suggested that the Australasian tektites have originated from an impact of a "diffuse object such as a comet." However, it is not easy to understand how the impact of a cometary nucleus would differ from that of an asteroid because upon passing through the atmosphere any cometary coma would be stripped off.…”
Section: Australasian Strewn Fieldmentioning
confidence: 99%
“…Barnes (e.g., Barnes and Pitakpaivan, 1962;Barnes, 1989Barnes, , 1990, mainly from studying Muong Nong-type tektites, suggested that the Australasian tektites have originated from an impact of a "diffuse object such as a comet." However, it is not easy to understand how the impact of a cometary nucleus would differ from that of an asteroid because upon passing through the atmosphere any cometary coma would be stripped off.…”
Section: Australasian Strewn Fieldmentioning
confidence: 99%
“…Tektites, glassy or crystalline bodies ranging in size from micrometers to 0.1 m, are ejecta from terrestrial impact craters (e.g., Taylor 1973;King 1977;Barnes 1990;Koeberl 1990). The majority of papers on tektites have been dedicated to determining the source of tektites or to attempting to discover the terrestrial crater from which they were ejected.…”
Section: Introductionmentioning
confidence: 99%
“…This may be the result oflower formation temperatures compared to splash-form tektites. They probably formed from the same or a very similar source material, but were less thoroughly heated (see e.g., Barnes, 1990, for petrographic evidence for this statement, based on vesicularity oflechatelierite particles) and have, therefore, lost less of their volatile element content than the splash form tektites. Muong Nong-type tektites may be the key to some important questions.…”
Section: Geochemistry and Petrography Of Tektitesmentioning
confidence: 92%